Combination of online clustering and Q-value based GA for reinforcement fuzzy system design. - Chia-Feng Juang (IEEE Transactions on fuzzy systems)
This paper proposes a combination of online clustering and Q-value based genetic algorithm (GA) learning scheme for fuzzy system design (CQGAF) with reinforcements. The CQGAF fulfills GA-based fuzzy system design under reinforcement learning environment where only weak reinforcement signals such as "success" and "failure" are available. In CQGAF, there are no fuzzy rules initially. They are generated automatically. The precondition part of a fuzzy system is online constructed by an aligned clustering-based approach. By this clustering, a flexible partition is achieved. Then, the consequent part is designed by Q-value based genetic reinforcement learning. Each individual in the GA population encodes the consequent part parameters of a fuzzy system and is associated with a Q-value. The Q-value estimates the discounted cumulative reinforcement information performed by the individual and is used as a fitness value for GA evolution. At each time step, an individual is selected according to the Q-values, and then a corresponding fuzzy system is built and applied to the environment with a critic received. With this critic, Q-learning with eligibility trace is executed. After each trial, GA is performed to search for better consequent parameters based on the learned Q-values. Thus, in CQGAF, evolution is performed immediately after the end of one trial in contrast to general GA where many trials are performed before evolution. The feasibility of CQGAF is demonstrated through simulations in cart-pole balancing, magnetic levitation, and chaotic system control problems with only binary reinforcement signals.